MiR-375 Inhibits Autophagy and Further Promotes Inflammation and Apoptosis of Acinar Cells by Targeting ATG7. Issue 4 (April 2020) - Zhao, Shang-Ping; Yu, Can; Xiang, Kai-Min; Yang, Ming-Shi; Liu, Zuo-Liang; Yang, Bing-Chang
Abstract : Objectives: MicroRNAs have been considered to be closely related with the development of severe acute pancreatitis (SAP), and microRNA-375 (miR-375) was believed to be a marker of SAP. We aim to investigate the role of miR-375 in regulating SP. Methods: Cerulein and lipopolysaccharide were used to establish the models of SAP. AR42J cell line was chosen for study in vitro. Flow cytometry was applied for assessing apoptosis. The contents of inflammatory factors were detected with related enzyme-linked immunosorbent assay and quantitative real-time polymerase chain reaction assays. Hematoxylin and eosin staining was applied to observe the pathological changes of pancreatic tissues. Immunohistochemistry analysis was conducted for investigating the expression of light chain 3. Results: The level of miR-375 in pancreatitis tissues and cell lines was upregulated. Overexpression of miR-375 promoted inflammation and the apoptosis of acinar cells through inhibiting autophagy. The binding site between miR-375 and ATG7 was identified, and miR-375 could directly regulate the ATG7. microRNA-375 suppressed autophagy and promoted inflammation and the apoptosis of acinar cells via targeting ATG7. Conclusions: We proved that miR-375 could inhibit autophagy and promote inflammation and the apoptosis of acinar cells through regulating ATG7. This study first proves that miR-375 modulates the development of SAP through targeting ATG7.